FISH PREDATORS OF THE GOLDEN MUSSEL Limnoperna fortunei IN DIFFERENT ENVIRONMENTS IN A SOUTH AMERICAN SUBTROPICAL RIVER - Sunshine de Ávila-Simas; David Augusto Reynalte-Tataje; Evoy Zaniboni-Filho (Boletim do Instituto de Pesca)
This study aimed to evaluate whether the golden mussel, Limnoperna fortunei, identified in the upper Uruguay River for the first time in 2012, has been incorporated into the diet of the ichthyofauna present in different environments of a Neotropical reservoir. To achieve this, we analyzed the digestive tract of fish that were collected seasonally between August 2015 and May 2016. The results showed that 22 fish species had L. fortunei in the digestive tract, of which 11 were previously not known to comprise the diet of this mollusk. Furthermore, it was observed that species belonging to the orders Characiformes and Cichliformes were the main consumers of L. fortunei in the lentic environment, whereas in the lotic and transition environments, the main consumers belonged to the order Siluriformes. The degree of digestion of L. fortunei in the digestive tract of fish indicated that although most fish could digest this food resource, some Siluriformes found it difficult. Thus, it can be concluded that the availability of L. fortunei in the upper Uruguay River forms a new food resource for the endemic ichthyofauna.